HealthStart : need for growth strategy - Jena, Sanjay Kumar, (SAGE Business Cases., 2018)
The case describes the launch of Healthstart, a company that specialises in accelerating and investing in healthcare start-ups. Healthstart conducted annual accelerator programs around healthcare entrepreneurship and selected start up received 2.5 million INR for 10% equity. In 2017 the CEO of Healthstart, Pradeep Jaisingh, is considering how to develop a sustainable business model and to increase the number of start-ups that Healthstart can invest in per year.